2018
DOI: 10.1111/dth.12735
|View full text |Cite
|
Sign up to set email alerts
|

Combining topical tretinoin with mometasone furoate in the treatment of vulvar lichen sclerosus: Results of dermoscopic assessment

Abstract: The main purpose of the present study was to compare the dermoscopic changes on vulvar lichen sclerosus (VLS) induced by two different 12‐week treatment protocols, namely mometasone furoate 0.1% ointment plus tretinoin 0.05% cream in short‐contact therapy (group A) versus the same corticosteroid plus emollient (group B). All dermoscopic images captured before and after treatment were assessed. Each dermoscopic variable selected for the study purpose was arbitrarily graded according to a 4‐point scale by dermat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Genital lichen sclerosus is a chronic inflammatory, immune‐mediated disease which is a recognized precursor of genital cancer 51–53 . Dermoscopy has been reported extensively in both sexes 22,54–60 . Whitish background and patchy structureless areas, varying in colour from white‐yellowish to milky‐pinkish, are the most prevalent dermoscopic features (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Genital lichen sclerosus is a chronic inflammatory, immune‐mediated disease which is a recognized precursor of genital cancer 51–53 . Dermoscopy has been reported extensively in both sexes 22,54–60 . Whitish background and patchy structureless areas, varying in colour from white‐yellowish to milky‐pinkish, are the most prevalent dermoscopic features (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has a bimodal age distribution; its incidence peaks at prepubertal and postmenopausal ages. Even though several environmental and genetic factors were accused, it is believed that autoimmunity and chronic inflammation play essential roles in its pathogenesis [8][9][10]. Karadag et al [11] investigated 350 LS patients, 98% of which had vulvar involvement, and reported that autoimmune antibodies (anti-thyroid, anti-nuclear, anti-mitochondrial antibodies) were detected in 22%.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that topical treatments were useful for pain relief in women with VLS [7][8][21][22]; however, these treatments did not necessarily lead to an improvement in sexual function. Two studies showed that topical immunomodulators could provide symptomatic relief and histopathological improvement in VLS patients [22,23], nevertheless, sexual dysfunction could be permanent despite these positive changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations